Association of life's essential 8 with chronic obstructive pulmonary disease: a population-based analysis of NHANES 2007-2018 - Yuhang Liu; Weidong Li; Jialing Tang; Siyao Gao (BMC, 2024)
Abstract Background Chronic obstructive pulmonary disease (COPD) is closely linked to cardiovascular diseases. We aimed to investigate the association between Life's Essential 8 (LE8), the newly established measurement to assess cardiovascular health (CVH), and COPD among U.S. general adults. Methods This study extracted the National Health and Nutrition Examination Survey (2007-2018) data. Multivariate logistic regression models were used to examine the associations between LE8 and COPD. A restricted cubic spline regression model was used to explore the dose-response relationships between LE8 scores and COPD. In addition, subgroup and sensitivity analyses were performed to assess the robustness of our results. Results Our study included 19,774 participants representing 145.2 million non-institutionalized U.S. population aged ≥ 20 years. The overall age-adjusted prevalence of COPD was 4.5%. After adjusting for the potential covariates, LE8 was inversely associated with COPD [adjusted odds ratio (AOR) = 0.169, 95% CI: 0.115, 0.249], exhibiting a nonlinear dose-response relationship (P for nonlinearity < 0.05). Similar trends in the associations of health behavior score (AOR = 0.300, 95% CI: 0.223, 0.404) and health factor score (AOR = 0.603, 95% CI: 0.426, 0.852) with COPD were also identified. Furthermore, higher LE8 metric scores of nicotine exposure and sleep health were associated with a lower prevalence of COPD. Conclusion LE8 was inversely associated with spirometric/self-reported COPD in a nonlinear trend, primarily driven by the nicotine exposure metric of LE8. Adhering to LE8 guidelines, especially smoking cessation, to sustain optimal CVH levels may be beneficial to alleviate the burden of COPD.